Estereótipos e representações dos corpos dos homens negros e os efeitos em suas construções identitárias - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The purpose of this research was to critically reflect on the experiences and identity constructions of black men in the midst of stereotypes and representations about their bodies and their lives. We sought through interviews, with some participants from different regions of the country and different perspectives, the narratives and perceptions of these subjects and their sociocultural implications in order to understand what it is to be a black man in our society. From these voices and with these voices we were able to discuss in more depth and seriousness the theme – intrinsically linked to studies on identity, stereotypes and representation (HALL, 2016; hooks, 2019; WOODWARD, 2011), racial issues (ALMEIDA, 2020; BENTO, 2022), and black masculinities (BOLA, 2020; FANON, 2008; PINHO, 2004; RESTIER & MALUNGO, 2019; SANTANA, MORJAN & CONCEIÇÃO, 2021; VIGOYA, 2018) – required. That said, we built the so-called "Black Men's Triad", an illustrative proposal based on the idea of ​​intersectionality (CRENSHAW, 2002), to help us identify the most latent crossings in the lives of black men, such as the violence, objectifications and affections that circulate in phases from childhood, adolescence to adulthood, and the consequences of these experiences. In addition, our study shed light on the discourses and images constructed and reproduced about black men from the Brazilian colonial period to the universe of traditional media and current social networks, aiming to identify the ways and means by which stereotypes and representations constituted part of the imaginary and power relations of our society.
Stereotypes and representations of black men's bodies and the effects on their identity constructions
Keywords: Homem negro - Estereótipos - Mídias; Homem negro - Representação - Mídias; Homem negro - Construção identitária - Mídias; Black man - Stereotypes - Media; Black man - Representation - Media; Black man - Identity construction - Media; CIENCIAS HUMANAS::SOCIOLOGIA